Lietuviškų knygų leidyba Rygoje 1904-1914 metais - Černiauskaitė, Violeta (Knygotyra, 1999)
Early in the 20th century, Riga had one of the largest Lithuanian colonies. Before World War I, there lived about 50 thousand Lithuanians. Due to the flexibility of the local administration in this multinational city and a more advanced economic and cultural atmosphere, the conditions for developing social and cultural activities for the Lithuanians were far more favorable than in Lithuania or any other center in the Russian Empire. Riga, with its prominent position in the book industry of Russia, had a considerable positive influence on the development of Lithuanian publishing and printing activities at that time. During the years 1904-1914, 250 Lithuanian books and brochures were published in Riga. However, the publishing of Lithuanian books there was notable for the fact that it was based almost solely on the initiative and private capital of L. Jakavičius and A. Macijauskas, and, therefore, inevitably acquired a distinct commercial character. Books published there often had poorer content due to the prevalent publications being adapted to the tastes of the mass reader. Nevertheless, through the organization of the publication of Lithuanian books and newspapers, the Lithuanian community in Riga managed to address not only urgent cultural and educational problems of local importance but also actively contributed to Lithuanian culture in general. Furthermore, some social and book publishing contacts between the Lithuanians and Latvians in Riga were very beneficial for the growth of Lithuanian culture and especially important for fostering the ideas of Lithuanian and Latvian national solidarity as a counterbalance to the influence of Polish culture.